THE VALUES OF BATANG HARING AS LOCAL WISDOM IN BUILD ING THE SUSTAINABLE COMPETITIVE ADVANTAGE OF TOURISM DESTINATION IN CENTRAL KALIMANTAN - Mau, Daniel Pandu; Sukawati, Tjokorda Gde Raka (Institut Pariwisata dan Bisnis Internasional, 2019)
As a regional tourism destination in Indonesia, Central Kalimantan has cultural richness from its sub-ethnics of Dayak (indigenous people in Kalimantan) that can be used to develop its tourism products. Therefore, through an ethnographic approach using triangulation data collection techniques, this study explored, illustrated and comprehended in-depth the culture of Central Kalimantan specifically local wisdom values. Batang Haring as a local wisdom of Dayak in Kalimantan, particularly Central Kalimantan, has culture value that is the balanced and harmonious relationship among three-dimensional: human, God, and nature implemented through rites of Kaharingan (traditional belief of Dayak). The uniqueness in implementing the values become a